Sharing as a first step to mainstream experience capitalization - Wanyoto, Anthony (Technical Centre for Agricultural and Rural Cooperation, 2019)
Experience Capitalization goes beyond writing success stories. You have to critically reflect on your project, and also write down why things didn't turn out as planned.